100th Anniversary of Macromolecular Science Viewpoint: Block Copolymer Particles: Tuning Shape, Interfaces, and Morphology - Shin, Jaeman J; Kim, Eun Ji; Ku, Kang Hee; Lee, Young Jun; Hawker, Craig J; Kim, Bumjoon J (ACS macro letters, 2020)
Confined assembly of block copolymers (BCPs) is receiving increasing attention due to the ability to create unconventional morphologies that cannot be observed in the corresponding bulk systems. This effect is further driven by the simplicity and versatility of these procedures for controlling the shape of particles prepared by 3D soft confinement of BCPs in emulsions. By taking advantage of a mobile emulsion interface, the one-step formation of nonspherical BCP particles through spontaneous deformation is possible with design principles and theoretical models for controlling shape/nanostructure now being established. This Viewpoint highlights strategies for shape tuning of BCP particles, currently accessible shapes, their controllability, and potential application. The emergence of 3D soft confinement of BCPs and related theory is overviewed with a focus on current strategies, types of nonspherical shapes achieved, and structure–property relationships for nonspherical BCP particles. Finally, the applications and future perspectives for these materials are discussed.